Potential application of light element stable isotope ratio in crude fiber for geographical origin verification of raw and cooked kabocha pumpkin (Cucurbita maxima). (30th March 2022) - Yoshida, Mitsuru; Tabata, Ayane; Niino, Takumi; Chiku, Kazuhiro; Nakashita, Rumiko; Suzuki, Yaeko
Highlights: δ 13 C and δ 18 O were used for geographical origin discrimination of kabocha pumpkin. Kabocha of Hokkaido, Japan was discriminated from those of Mexico and New Zealand. δ 13 C and the δ 18 O of flesh were affected by seasonings after cooking or processing. Effects of seasonings on δ 13 C and δ 18 O were eliminated by extracting crude fiber. δ 13 C and δ 18 O of crude fiber can be used for verification even after cooking. Abstract: In this study, we investigated the possibility of the geographical origin discrimination between Japanese and Mexican kabocha pumpkin using δ 13 C and δ 18 O in lyophilized raw flesh. Kabocha harvested in Hokkaido, the major kabocha production area in Japan, could be discriminated against not only that grown in Mexico but also that in New Zealand. However, seasoning after cooking or processing affected the δ 13 C and the δ 18 O values. Crude fiber extraction eliminated the effect of seasonings and enabled the adoption of the δ 13 C and δ 18 O values in crude fiber for the geographical origin verification of kabocha even after cooking and processing. The usage of δ 13 C and the δ 18 O in crude fiber would extend the application possibilities of stable isotope analysis in the geographical origin determination of various cooked and processed vegetables and fruits as well as raw materials.